DISTRIBUTION AND ECOLOGY OF LUTRA LUTRA ( L INNAEUS, 1758) I N KIZILIRMAK RIVER ( TURKEY) - K. Toyran; . Albayrak (Journal of Animal and Plant Sciences, 2019)
This study was conducted in an about 130-km section of Kızılırmak River located between Hirfanlı Dam and border of Kalecik district between February 2005 and August 2009. Footprints and feces of otter were identified and direct observations were made in order to determine its activity areas (including 7 localities). As a result of analysis of 233 fecal samples of otter, preys in its diet were divided into 5 categories as invertebrates, fish, bird, mammal, and unidentified pieces. It was determined that 69.91% of the diet were fish, 18.80% were invertebrate, 4.39% were bird, 4.39% were mammal, and 2.51% were unidentified remains. Habitat characteristics were recorded and habitat quality was calculated for Lutra lutra. Behaviors of Eurasian otter individuals determined as a result of the direct observation were recorded and photos were taken.
Keywords: Otter; Lutra lutra; Distribution; K1z1l1rmak River; K1r1kkale Province; TurKey